Preference for caesarean and attitudes toward birth in a Chilean sample of young adults. Issue 2 (March 2020) - Weeks, Fiona H.; Sadler, Michelle; Stoll, Kathrin
Abstract: Background: Little empirical research exists about what motivates birth mode preferences, and even less about this topic in Latin America, where obstetric interventions and caesareans are some of the highest worldwide. Aim: To identify factors associated with caesarean preference among Chilean men and women who plan to have children and to inform childbirth education and informed consent procedures. Methods: An online cross-sectional survey measuring attitudes toward birth was administered to graduate students at a large public university in Chile. Eligible students were under the age of 40 and had no children but intended to have children. Logistic regression modelling was used to determine which sociodemographic factors, knowledge and beliefs were associated with caesarean preference. Findings: Among eligible students, 730 responded and 664 provided complete answers to the variables of interest. Respondents had a mean age of 28.8; 38% were male and 62% female. Positive attitude toward technological intervention (Odds Ratio 7.4, 95% Confidence Interval 3.9–14.0), high risk perception of vaginal birth (Odds Ratio 1.8, 95% Confidence Interval 1.1–2.8), family history of caesarean (Odds Ratio 1.9, 95% Confidence Interval 1.0–3.8) and high fear of birth (Odds Ratio 3.7, 95% Confidence Interval 2.0–6.8) were associated with caesarean preference. Discussion: Preference for caesarean birth was highly associated with positive attitudes toward technological intervention and may be related to a lack of knowledge about the realities of caesarean and vaginal birth. Conclusions: Patient-centered education on the relative benefits and risks of birth modes has the potential to influence preferences toward vaginal birth.